The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/00019442-200505000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Onset of Posttraumatic Stress Disorder Among Male Combat Veterans: A Case Series

Abstract: Environmental stressors, coupled with age-related neurodegeneration, may potentially contribute to the late-life recrudescence or emergence of PTSD symptoms in veterans exposed to combat-related trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…The most convincing evidence for delayed-onset PTSD was from three motor vehicle accident victims who were under continuing medical care for their physical injuries prior to onset, making detection of symptoms in the posttrauma period more likely if present (12,13). In the six studies describing elderly war veterans with very long intervals to first onset, 18 of the 22 cases were corroborated by someone else, in most cases a relative and usually the spouse (15,19,20). Given the age of the veterans, this does not rule out the possibility of episodes in the early months or years posttrauma that might have gone undisclosed or been forgotten, a limitation noted in two studies (20,15).…”
Section: Case Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…The most convincing evidence for delayed-onset PTSD was from three motor vehicle accident victims who were under continuing medical care for their physical injuries prior to onset, making detection of symptoms in the posttrauma period more likely if present (12,13). In the six studies describing elderly war veterans with very long intervals to first onset, 18 of the 22 cases were corroborated by someone else, in most cases a relative and usually the spouse (15,19,20). Given the age of the veterans, this does not rule out the possibility of episodes in the early months or years posttrauma that might have gone undisclosed or been forgotten, a limitation noted in two studies (20,15).…”
Section: Case Studiesmentioning
confidence: 98%
“…Of the 10 studies that met inclusion criteria for review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), seven reported delayed-onset PTSD in relation to war experiences (14)(15)(16)(17)(19)(20)(21) and three in relation to motor vehicle accidents (12,13,18). Four of the studies used DSM-IV diagnostic criteria, which include clinically significant distress or impairment in social, occupational, or important areas of functioning (criterion F).…”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Case studies suggest that this form of PTSD may arise in elderly individuals as they begin to cognitively decline (Johnston 2000;Mittal et al 2001;Ruzich et al 2005;van Achterberg et al 2001). A vivid example concerned a 95-year-old woman who had probable Alzheimer's disease (van Achterberg et al 2001).…”
Section: Does Traumatic Stress Cause Brain Damage?mentioning
confidence: 99%